I'll be gone in the dark eaudiobook One woman's obsessive search for the golden state killer. - McNamara, Michelle (2018)
THE BASIS FOR THE MAJOR 6-PART HBO® DOCUMENTARY SERIES #1 NEW YORK TIMES BESTSELLER A BEST BOOK OF THE YEAR: Washington Post | Maureen Corrigan, NPR | Paste | Seattle Times | Entertainment Weekly | Esquire | Slate | Buzzfeed | Jezebel | Philadelphia Inquirer | Publishers Weekly | Kirkus Reviews | Library Journal | Bustle Winner of the Goodreads Choice Awards for Nonfiction | Anthony Award Winner | SCIBA Book Award Winner | Finalist for the Edgar Award for Best Fact Crime | Longlisted for the Carnegie Medal for Excellence The haunting true story of the elusive serial rapist turned murderer who terrorized California during the 70s and 80s, and of the gifted journalist who died tragically while investigating the case—which was solved in April 2018. The haunting true story of the elusive serial rapist turned murderer who terrorized California for over a decade—and of the gifted journalist who died tragically while investigating the case. Introduction by Gillian Flynn Afterword by Patton Oswalt "A brilliant genre-buster.... Propulsive, can't-stop-now reading. " —Stephen King For more than ten years, a mysterious and violent predator committed fifty sexual assaults in Northern California before moving south, where he perpetrated ten sadistic murders. Then he disappeared, eluding capture by multiple police forces and some of the best detectives in the area. Three decades later, Michelle McNamara, a true crime journalist who created the popular website TrueCrimeDiary.com, was determined to find the violent psychopath she called ""the Golden State Killer."" Michelle pored over police reports, interviewed victims, and embedded herself in the online communities that were as obsessed with the case as she was. I'll Be Gone in the Dark—the masterpiece McNamara was writing at the time of her sudden death—offers an atmospheric snapshot of a moment in American history and a chilling account of a criminal mastermind and the wreckage he left behind. It is also a portrait of a woman's obsession and her unflagging pursuit of the truth. Utterly original and compelling, it is destined to become a true crime classic—and may at last unmask the Golden State Killer. Cover Art 2020 © Home Box Office, Inc. All Rights Reserved. HBO is service marks of Home Box Office, Inc.